(untitled) (Bangladesh Pharmaceutical Journal, 2024)
In the traditional systems of medicine, Clerodendrum viscosum (CV) has important medicinal uses for the treatment of asthma, ulcer, inflammation, pyrexia, diabetes etc. In this study, analgesic, anti-inflammatory, neuropharmacological and antidiabetic effect of root extract of C. viscosum (CV) was investigated. Mice (Swiss albino) of either sex of 25-30 g were distributed into 4 groups as control (normal water), standard (STD), CV 250 mg/kg and CV 500 mg/kg (n=6). Analgesic effect was investigated by acetic acid initiated writhing test, formalin initiated paw licking test and hot plate test. Anti-inflammatory effect was investigated by xylene and croton oil initiated ear edema test and cotton pellet pleurisy test. Pentobarbital mediated sleeping time and hole cross tests were applied to assess neuro-pharmacological activity. Antidiabetic effect was evaluated by in-vitro alpha amylase inhibitory assay. In the acetic acid initiated writhing test, formalin test and hot plate test, the alcoholic extract of root showed significant antinociceptive activity (p<0.01) at 500 mg/kg dose. The test extract lowered inflammation in xylene, croton oil and cotton pellet test which was significant (p<0.001). The 500 mg/kg dose significantly (p<0.001) increased onset time of sleeping and significantly reduced sleeping duration (p<0.01) in sleeping time test. It also showed insignificant effect in hole-cross test. The extract exhibited a good alpha amylase inhibitory potential (IC50=1.24 mg/ml). C. viscosum root exhibited analgesic, anti-inflammatory, antidiabetic as well as CNS stimulant effect in model mice used for experimental purpose. More investigations are needed for the evaluation of such activities as well as the potential of this plant. Bangladesh Pharmaceutical Journal 27(2): 164-174, 2024 (July)